In vitro analysis of multistage carcinogenesis. - Nettesheim, P (1987)
Several key events in the multistep process of neoplastic transformation of rat tracheal epithelium (RTE) are described. Whether tracheal epithelium is exposed in vivo to carcinogenic agents or whether primary tracheal epithelial cells are exposed in vitro to carcinogens, initiated stem cells can be detected soon after the exposure by their ability to grow under selective conditions in culture. These initiated stem cells differ fundamentally from normal stem cells in their response to factors normally constraining proliferation and self-renewal. Thus, disruption of inhibitory control mechanisms of stem cell replication appears to be the first event in RTE cell transformation. While the probability of self-renewal (PSR) is clearly increased in initiated stem cells, most of the descendants derived from such stem cells differentiate and become terminal and do not express transformed characteristics. Progression from the first to the second stage of RTE cell transformation, the stage of the immortal growth variant (IGV), is characterized by loss of responsiveness to the growth-restraining effects of retinoic acid. In the third stage of neoplastic transformation, the stage during which neoplastic growth variants (NGV) appear, a growth factor receptor gene is inappropriately expressed in some of the transformants. Thus, it appears that loss of growth-restraining mechanisms may be an early event, and activation of a growth stimulatory mechanism a late event, in neoplastic transformation of RTE cells.